2022
DOI: 10.1177/10547738211069725
|View full text |Cite
|
Sign up to set email alerts
|

Short Breastfeeding Duration is Associated With Premature Onset of Female Breast Cancer

Abstract: Currently, there is controversy concerning potential factors that contribute to the development of breast cancer. Our study analyzed the possible association between weight status, cigarette consumption, lactation period, serum estrogen levels, family history of breast cancer, and age at breast cancer diagnosis. We conducted a retrospective study at a University Hospital in Granada (Spain) by consulting the medical records of 524 women aged 19 to 91 years, all of them diagnosed and treated for breast cancer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In other words, women with a family history of breast cancer were diagnosed at a mean age of 55 years. Thus, maternal lactation appears to have a potential protective effect on breast cancer (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, women with a family history of breast cancer were diagnosed at a mean age of 55 years. Thus, maternal lactation appears to have a potential protective effect on breast cancer (11).…”
Section: Resultsmentioning
confidence: 99%
“…In two of the three studies examining the effect of breastfeeding on breast cancer in women with a positive history, breastfeeding did not appear to be a protective factor. More specifically, the study by Fernandez-Aparicio A et al (2022) concluded that the effect of family history was stronger than the protective effect of breastfeeding, as women with a family history of breast cancer with a breastfeeding duration of more than three months had an average age of diagnosis of 55 years, while those with no family history and a breastfeeding duration of more than three months had an average age of diagnosis of about 70 years (11). However, in the study by Lin H et al (2019) there appeared to be a synergistic effect of breastfeeding and family history on breast cancer risk, with participants who did not breastfeed and had a positive family history having a higher risk of breast cancer (OR: 2.630, 95%) (25).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were conducted in the USA, [16,21,27,31] two in Spain, [18,22] two in India, [20,30] one in Serbia, [17] one in Sweden, [19] one in Norway, [23] one in Iran, [24] one in Iceland, [25] one in Tunisia, [26] one in Brazil, [28] one in Germany, [29] and one in Sil Lanka. [32] Eleven studies were case-control, [17,20,[24][25][26][27][28][29][30]32] six were retrospective in nature, [16,18,[21][22][23]31] and one was a prospective study. [19] Patients with a family history of breast cancer ranged from 1.25% [26] to 55%.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…[19] Patients with a family history of breast cancer ranged from 1.25% [26] to 55%. [22] All included studies reported that breastfeeding and its longer duration play a protective role against breast cancer and significantly decrease its incidence.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The risks contributing to BC's development include genetic and non-genetic factors. Genetic factors include mutations in susceptibility genes such as BRCA1 and BRCA2 [ 6 , 7 ] non-genetic factors include reproductive and hormonal risks such as early age at menarche, late menopause, short breastfeeding periods, and obesity [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%